2018
DOI: 10.1111/aos.13642
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related change and sex difference over 60s in disc‐fovea angle in Japanese population: the Nagahama Study

Abstract: Larger DFA in women than in men in their 60s and 70s suggests the possibility that age-related excyclo-shift occurs more easily in postmenopausal women compared to men of the same age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…This nding is consistent with the earlier studies that reported that the population is greater in excyclodeviation than incyclodeviation. 3,7,32 Therefore, we consider that it may better to apply our model only to the excyclodeviation until enough subjects with incyclodeviation are accumulated. Our model can detect between excyclodeviation and incyclodeviation from the plus and minus signs calculated from the difference between the fovea and ONH.…”
Section: Discussionmentioning
confidence: 99%
“…This nding is consistent with the earlier studies that reported that the population is greater in excyclodeviation than incyclodeviation. 3,7,32 Therefore, we consider that it may better to apply our model only to the excyclodeviation until enough subjects with incyclodeviation are accumulated. Our model can detect between excyclodeviation and incyclodeviation from the plus and minus signs calculated from the difference between the fovea and ONH.…”
Section: Discussionmentioning
confidence: 99%
“…First, the study was only performed in participants aged around 20 years. Miyata et al 16 evaluated the age-related changes in DFA in the Nagahama study and reported that older people had larger DFA than younger people and tended to exhibit exocyclic rotation according to age. Further studies are warranted among participants with various ages and glaucoma patients to examine the incidence of cyclodeviation.…”
Section: Discussionmentioning
confidence: 99%
“…Several methods have been used for measuring the objective cyclodeviation including artificial markers such as physical markers, corneal tattoo, scleral markings, 6 7 search coil, 8 tracking system on an excimer laser, 9 the iris pattern imaging 10 and fundus imaging. [11][12][13][14][15][16][17][18][19] In this study, we used fundus photography to reproduce the conditions similar to that during OCT. Thereby, we aimed to assess the differences and variations in the angle of cyclodeviation under binocular opening situation and monocular occlusion.…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…The inter-eye difference of the fovea–to-disc angle in normal subjects was observed previously in a range of 0.0° to 4.4° based on fundus photographs by Bixenman and von Noorden [ 20 ], and more recently as a mean of 1.15° ± 1.39° by Jethani et al [ 22 ]. The fovea-to-disc angle followed a normal distribution in a population-based study [ 23 ]. Therefore, we used a range covering approximately 95% of the data which falls within two standard deviations of the mean of normal subjects reported by Jethani et al as a reference value (3.93°) for determining whether the fundus excyclotorsion was symmetric or asymmetric.…”
Section: Methodsmentioning
confidence: 99%